High temperature dyeing of PET fabric with natural colourants extracted from annatto seeds. Issue 2 (21st February 2019) - Nakpathom, Monthon; Somboon, Buppha; Narumol, Nootsara; Mongkholrattanasit, Rattanaphol
Abstract : Purpose: The purpose of this study is to investigate the possibility of dyeing polyester (PET) fabric with natural dye extracted from annatto seeds using high temperature dyeing method. Design/methodology/approach: PET fabric was dyed with annatto extract by varying dyeing parameters (temperature, time, pH and dye concentration) to determine the optimum dyeing conditions. The influences of KAl(SO4 )2, FeSO4, gallnut mordants or a commercial UV absorber on colour yield and fastness properties were further studied. Findings: Optimum results were obtained when the fabric was dyed at 130°C for 30 min in a dyebath containing 15 per cent (owf) annatto dye at pH 6. The dyed fabric had an orange shade and exhibited good to excellent wash, crock, perspiration fastness and fair light fastness. Further dyeing with mordants or UV absorber mostly resulted in lower colour yield and similar fastness properties. Research limitations/implications: Although the light fastness was slightly improved to moderate level for the sample with UV absorber, a noticeable colour staining on cotton portion of multi-fibre fabric occurred when subjected to standard washing test. Compared to C.I. Disperse Orange 73, the annatto dye exhibited comparable colour fastness but had inferior light fastness when dyed at approximately the same colour strength. Originality/value: Natural colourants from annatto seeds can be used to dye PET fabric at high temperature without mordants, yielding deep orange shade and satisfactory fastness properties. This study provides a promising application to reduce the environmental impact of synthetic dyes.